Enhancement on oral absorption of paclitaxel by multifunctional pluronic micelles. (February 2013) - Li, Yimu; Bi, Yiling; Xi, Yanwei; Li, Lingbing
<x xml:space="preserve">Abstract</x> The aim of the present study is to synthesize Pluronic F127-polyethylenimine-folate (PF127-PEI-FA) copolymer, construct a mixed micelle system with PF127-PEI-FA copolymer and Pluronic P123 (PP123) and to evaluate the potential of these mixed micelles as an oral drug delivery system for paclitaxel (PTX). The results of intestinal absorption revealed that the PTX-loaded micelles displayed superior permeability across intestinal barrier than free drug and PF127-PEI-FA/PP123 mixed micelles exhibited the strongest permeability across intestinal barrier. These results were also proved by the studies on cytotoxicity and cell uptake tests. The mechanism was demonstrated in connection with inhibition of the efflux mediated by intestinal P-glycoprotein (P-gp) and enhancement of the electrostatic interaction of positive micelles with the negative intestinal epithelial cells, thereby promoting the permeation across the intestinal wall. The presence of verapamil and Pluronic both improved the intestinal absorption of PTX, which further certified the effect of Pluronic on P-gp inhibition. Pharmacokinetic study demonstrated that the area under the plasma concentration-time curve (AUC0→36 h) of PTX-loaded micelles was three times greater than the PTX solution (dissolved in a 50/50 (vol/vol) mixture of Cremophore EL/dehydrated ethanol) (p < 0.05). In general PF127-PEI-FA/PP123 mixed micelles were proved to be potential oral drug delivery system for PTX.